(untitled) (Proceedings of the International Conference on Public Health, 2019)
The growth of drinking water refill service business in Indonesia is one of the most promising and growing business in recent years. On the other hand, along with the conditions of diarrhea cases in this region remain concerned. This research aimed to identify spatially the influence of the existence of refilling water depots and the quality of its products to the incidence of diarrhea in Tanah Bumbu District. The study held in Kota Pagatan, sub district of Kusan Hilir District of Tanah Bumbu in November-December 2017. Water samples are taken at every depot with complete procedure and marked spatially then sample was assessed microbiologically to determined E.coli and Coliform contamination. The bacteria-positive depot on examination of the sample is categorized as ’contaminated’ contrarily no bacteria depot is categorized as ’clean’. Diarrhea case data in the area of ​​the data was taken from 2016 research data in the form of respondent data, location and household characteristics related to patient’s family status and access to drinking water. Furthermore, the two types of data are integrated into spatial analysis to analyze the spatial relation of the depot’s water quality with the distribution of diarrhea cases. There is a spatial suitability between the density of the depots’ position and the density of the diarrheal cases found. The concentration of ’contaminated’ depot has a significant effect on the characteristic profile of the most of patients who were in the vicinity of the depot.